2014
DOI: 10.1007/s13197-014-1328-4
|View full text |Cite
|
Sign up to set email alerts
|

Safety and quality parameters of ready-to-cook minced pork meat products supplemented with Helianthus tuberosus L. tubers fermented by BLIS producing lactic acid bacteria

Abstract: The aim of this study was to evaluate the influence of additives of Jerusalem artichoke (JA), fermented with P. acidilactici KTU05-7, P. pentosaceus KTU05-9, L. sakei KTU05-6, on the quality and safety parameters of ready -to cook -minced pork (RCMP). Fermented JA additives reduced pH of the meat products and decreased water holding capacity (WHC) from 2.01 till 2.93 %. Concentrations of biogenic amines in RCMP with additives of the lactic acid bacteria (LAB) -fermented JA were significantly lower comparing wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The BLIS-producing LAB strains, P. acidilactici KTU05-7, P. pentosaceus KTU05-9, and L. sakei KTU05-6, were used to ferment the plant (Jerusalem artichoke, Helianthus tuberosus L.), and 5% of the fermented products were tested to inhibit the food-borne pathogen at 18 • C for 12 h in ready-to-cook (RTC) minced pork [115]. As a result, the P. acidilactici fermented product presented the highest antimicrobial activity compared to the other strains.…”
Section: Bacteriocin-like Inhibitory Substance (Blis)mentioning
confidence: 99%
“…The BLIS-producing LAB strains, P. acidilactici KTU05-7, P. pentosaceus KTU05-9, and L. sakei KTU05-6, were used to ferment the plant (Jerusalem artichoke, Helianthus tuberosus L.), and 5% of the fermented products were tested to inhibit the food-borne pathogen at 18 • C for 12 h in ready-to-cook (RTC) minced pork [115]. As a result, the P. acidilactici fermented product presented the highest antimicrobial activity compared to the other strains.…”
Section: Bacteriocin-like Inhibitory Substance (Blis)mentioning
confidence: 99%
“…As a result, powder/gelled inulin and/or carbonate used in the formulation were marked to show the potential to meet the effects of phosphates on the microbial load during storage. Previously, Stimbirys et al () reported that fermented Jerusalem artichoke (inulin source) was effective to reduce the number of pathogenic bacteria in artificially contaminated meat samples. Avila‐Reyes, Garcia‐Suareza, Jimenez, San Martín‐Gonzalezc, and Bello‐Perez () also stated that utilization of prebitoic colloids such as inulin could be suitable for protecting Lactobacillus.…”
Section: Resultsmentioning
confidence: 99%
“…Besides their technological, functional, and antioxidative impacts, phosphates are also regarded as indirect antimicrobials, mainly affecting gram-positive bacteria, some micromycets, and yeast cells Previously, Stimbirys et al (2015) reported that fermented Jerusalem artichoke (inulin source) was effective to reduce the number of pathogenic bacteria in artificially contaminated meat samples. Avila-Reyes, Garcia-Suareza, Jimenez, San Martín-Gonzalezc, and Bello-Perez (2014) also stated that utilization of prebitoic colloids such as inulin could be suitable for protecting Lactobacillus.…”
Section: Microbiological Countsmentioning
confidence: 99%
“…It is widely used in food production as an additive not only to pastries, but also to meat, dairy and other products. Food products fortified with microelements make the immune system of the human body stronger [33,34]. In addition, Jerusalem artichoke is rich in inulin, which promotes calcium absorption and lipid metabolism, improving the health status of a person having a product with this additive in it as a meal, and reducing the risk for many health problems, including cardiovascular ones [35].…”
Section: Discussionmentioning
confidence: 99%